2012
DOI: 10.3923/pjbs.2012.147.151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vitamin D Deficiency and Secondary Hyperparathyroidism in Obese and Non-obese Children and Adolescents

Abstract: Obesity subjects individuals into metabolic and endocrine disorders. Thus obesity may increase the risk of vitamin D deficiency. This text aims at studying the prevalence of vitamin D deficiency and secondary hyperparathyroidism in obese children. In a non-randomized case control study on 52 obese children (body mass index (BMI) >95th percentile) aged 4 to 16 years undertaken at the outpatient endocrine clinic of the Children Hospital at Tabriz University between 2009-2011. This study was conducted to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…[29][30][31][32][33] In the worst cases, the hypovitaminosis D causes skeletal consequences such as rickets, in the young, and osteomalachia in the adult. [34][35][36][37] Moreover, it seems to be related to nonskeletal manifestations, as enhanced risk of chronic disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] In the worst cases, the hypovitaminosis D causes skeletal consequences such as rickets, in the young, and osteomalachia in the adult. [34][35][36][37] Moreover, it seems to be related to nonskeletal manifestations, as enhanced risk of chronic disease and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed in Table 2 30 , 82 - 91 , 93 , 97 - 104 most studies reported mean 25(OH)D levels in teens or close to 20 ng/ml, thus again revealing a large proportion of apparently healthy children, that is 30–75%, to have 25(OH)D levels below this deemed desirable cut-off.…”
Section: Magnitude Of the Problem And Predictors Of Low Vitamin D Statusmentioning
confidence: 98%
“…Consistent predictors across these studies for lower values were age, albeit with differing findings, some studies showing older age to be a risk factor, 57 , 67 , 69 while others point to younger age, 41 , 42 , 77 female gender in adults 41 , 61 , 63 , 72 , 75 , 82 and children, 83 - 89 winter season, sunlight exposure and veiling, 40 , 41 , 44 , 56 , 60 , 63 , 66 , 75 , 78 , 81 , 90 , 92 except in some studies from gulf countries where summer registers lowest values in studies from the United Arab Emirates, 75 , 77 pollution, 43 low calcium or vitamin D dietary intake, 67 , 77 , 80 , 81 , 90 , 92 and exclusive breast feeding in infants 88 . Other predictors included high BMI and /or increased adiposity, 39 , 60 , 66 - 68 , 72 , 93 and lower SES status or educational level 44 , 60 , 64 , 68 , 80 , 83 .The impact of menopause was not consistent across studies, whereas premenopausal women had higher levels in the study from Saudi Arabia, 67 the opposite was found in UAE 77 Table 1. details studies conducted in adults, Table 2 in children, Table 3 in mothers-neonates, by country, and highlights are underscored here-in.…”
Section: Magnitude Of the Problem And Predictors Of Low Vitamin D Statusmentioning
confidence: 99%
“…1,25(OH) 2 D 3 is widely used as an antiresorptive agent for the management of 1,25(OH) 2 D 3 deficiency and secondary hyperparathyroidism in children and adolescents (Ghergherechi et al 2012;Alshamsan and Bin-Abbas 2016;Dura-Trave and Gallinas-Victoriano 2016). Though vitamin D is necessary for basal bone homeostasis, excessive concentrations may be harmful.…”
Section: Introductionmentioning
confidence: 99%